Assessing tourist experience and willingness to pay for biodiversity conservation at Mongkrang Hill, Mount Lawu, Central Java, Indonesia - ARDITA AYU WULANDARI; ARUM NUR MUKARROMAH; ASFI DZIHNI; ATIKAH KHOIRIYAH AZZAM; ANGGUN DERISTANI; SUNARTO SUNARTO; AHMAD DWI SETYAWAN (Smujo International, 2025)
Abstract. Wulandari AA, Mukarromah AN, Dzihni A, Azzam AK, Deristani A, Sunarto, Setyawan AD. 2025. Assessing tourist experience and willingness to pay for biodiversity conservation at Mongkrang Hill, Mount Lawu, Central Java, Indonesia. Nusantara Bioscience 17: 277-288. Highland ecosystems are ecologically sensitive environments increasingly pressured by nature-based tourism. Mongkrang Hill, located on the southern slopes of Mount Lawu in Karanganyar District, Central Java, Indonesia, has experienced rapid visitor growth, raising concerns regarding vegetation disturbance, waste accumulation, and declining habitat quality. This study assesses tourist experience and Willingness to Pay (WTP) for conservation by integrating the Experiential Value Scale (EVS) with economic valuation. A total of 60 visitors were surveyed using structured questionnaires, supported by field observations and semi-structured interviews. Multiple regression analysis showed that all four EVS dimensions—hedonic, novelty, interaction, and comfort—significantly influenced visitor satisfaction, with novelty and hedonic value being the strongest predictors. Satisfaction, in turn, had a positive and significant effect on WTP (? = 0.90), explaining 80.1% of its variance. The average additional WTP of IDR 15,840 indicates substantial potential for conservation-based financing. Observations further revealed ecological pressures related to trail erosion, vegetation trampling, and improper waste disposal, alongside community benefits through local economic activities and circular economy practices such as plastic waste recycling. The integrated EVS–WTP approach highlights how enhanced visitor experience can strengthen pro-conservation behavior and provide actionable pathways for sustainable ecotourism management. These findings support the development of experience-based conservation strategies for biodiversity protection in highland ecosystems.